Influência da fenologia no desenvolvimento e fisiologia das galhas de Eriogallococcus gen. nov. em Pseudobombax grandiflorum (Cav.) A. Robyns (Malvaceae) - Thiago Alves Magalhaes (2010)
One of the important factors in the interactions that ends up in the development of galls is the adjustment of the herbivore life cycle to that of its host plant. This adjustment is especially important when the system involves deciduous plants, such as that of Eriogalococcus-Pseudobombax grandiflorum system. The study of this system revealed the existence of phenological synchrony between the host plant and the galling herbivore, which is vital to the maintenance of the galling species. Unlike commonly found in Eriococcidae, the sexual dimorphism of the galling herbivores is not reflected in gall morphotype, also there are subtle anatomical differences between galls induced by male and female, namely, the shape of the nymphal chamber and the cells of its dermal system. Regardless the sex of the inducers, the galls are green, glabrous, intralaminar, with a needle-like projection to the adaxial surface, and an ostiole facing the abaxial surface. By structural evaluation, we could conclude that there is an influence of the shape on the function of photosynthetic tissues, since the percentage of chlorophyllous tissue and chlorophyll content were lower in galls, and did not differ between galled and non galled leaflets. The galling herbivore manipulate the chemical composition of its host plant within its metabolic limits, which is inferred by the similarity between the histochemical profiles of non galled tissues and galls.